2021
DOI: 10.1038/s41467-021-25795-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 427 genomes reveals moso bamboo population structure and genetic basis of property traits

Abstract: Moso bamboo (Phyllostachys edulis) is an economically and ecologically important nontimber forestry species. Further development of this species as a sustainable bamboo resource has been hindered by a lack of population genome information. Here, we report a moso bamboo genomic variation atlas of 5.45 million single-nucleotide polymorphisms (SNPs) from whole-genome resequencing of 427 individuals covering 15 representative geographic areas. We uncover low genetic diversity, high genotype heterozygosity, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Bamboo is an important non-woody forest resource rich in natural lignocellulose. The global annual output of bamboo is about 1.5 billion, and continuously regenerated bamboo is an important alternative resource for about 1/2 of the annual wood gap (250 million m 3 ) [1,2]. China is one of the distribution centers of bamboo plants, ranking first in the world in terms of bamboo species, storage, and area [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo is an important non-woody forest resource rich in natural lignocellulose. The global annual output of bamboo is about 1.5 billion, and continuously regenerated bamboo is an important alternative resource for about 1/2 of the annual wood gap (250 million m 3 ) [1,2]. China is one of the distribution centers of bamboo plants, ranking first in the world in terms of bamboo species, storage, and area [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The Ka/Ks proportion went from 0.1415 to 0.3605, and the Ka/Ks ratio of the 10 duplicated PheNAP1 gene pairs were less than 1, demonstrating that these genes underwent a purification selection of evolution. The analysis of 427 moso bamboo individuals, 12 PheNAP1 genes were found, showing low genomic diversity [ 16 ]. Only PheNAP1:4 may be affected by structural variants (SVs), and PheNAP1:7 was detected in the long, continuous, heterozygous, SNP-clustered regions of high frequency in Chr.7: 38,000,001–44,200,000.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that if more than two alleles of the two genes were edited, the transgenic plants appeared albino (Wang et al, 2020). Moso bamboo is considered to be an allotetraploid with high genotype heterozygosity (Guo et al, 2019;Zhao et al, 2021). For genome editing, the homologous and subgenome sequences should be considered to designate precise target sites.…”
Section: Discussionmentioning
confidence: 99%
“…This species is characterized by asexual reproduction, rapid growth, and a high carbon fixation capacity (Zhou et al, 2011). Recently, an analysis of 427 genomes has revealed the low genetic diversity of the moso bamboo population, which indicates that this species may have a low effective population size and a small genetic pool that can be used for future breeding purposes (Zhao et al, 2021). Unfortunately, due to the long and unpredictable flowering cycle of bamboo, it is difficult to obtain new varieties through crossbreeding.…”
Section: Introductionmentioning
confidence: 99%